The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1128/jvi.00749-17
|View full text |Cite
|
Sign up to set email alerts
|

Pseudorabies Virus US3-Induced Tunneling Nanotubes Contain Stabilized Microtubules, Interact with Neighboring Cells via Cadherins, and Allow Intercellular Molecular Communication

Abstract: Tunneling nanotubes (TNTs) are long bridge-like structures that connect eukaryotic cells and mediate intercellular communication. We found earlier that the conserved alphaherpesvirus US3 protein kinase induces long cell projections that contact distant cells and promote intercellular virus spread. In this report, we show that the US3-induced cell projections constitute TNTs. In addition, we report that US3-induced TNTs mediate intercellular transport of information (i.e. GFP) in the absence of other viral prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 48 publications
1
56
0
Order By: Relevance
“…This phenomenon might also function as a working hypothesis in the case of viral transport mediated by TNTs: while examining the dual-color mutant trafficking in live cells, we did not directly detect two-color structures inside TNTs (although that may have been the result of how the viral particle was positioned in the tube), and the two signals appeared to travel separately in the nanotubes. However, the presence of intact virions in nanotubes was reported for projections formed by pseudorabies virus (PRV)-infected cells (53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon might also function as a working hypothesis in the case of viral transport mediated by TNTs: while examining the dual-color mutant trafficking in live cells, we did not directly detect two-color structures inside TNTs (although that may have been the result of how the viral particle was positioned in the tube), and the two signals appeared to travel separately in the nanotubes. However, the presence of intact virions in nanotubes was reported for projections formed by pseudorabies virus (PRV)-infected cells (53).…”
Section: Discussionmentioning
confidence: 99%
“…PRV studies have indicated for the first time that Us3 protein kinase, a protein that is highly conserved among herpesviruses, stimulates the formation of long intercellular projections (54). While this manuscript was being edited for submission, another report about the possible role of tunneling nanotubes in alphaherpesvirus infection was published (53). The authors demonstrated that cells infected with pseudorabies virus or transfected with PRV Us3 produced TNT-type projections involved in the transport of viral proteins and viral particles.…”
Section: Discussionmentioning
confidence: 99%
“…TMTs in our DHPC-018 cells also contain microtubules and intermediate filaments. While microtubules are absent from some TNTs (Rustom et al, 2004;Sowinski et al, 2008;Wang et al, 2010;Desir et al, 2018;Kretschmer et al, 2019), they are present in others (Önfelt et al, 2006;Osswald et al, 2015;Jansens et al, 2017;Sáenz-de-Santa-María et al, 2017;Resnik et al, 2018;Zhang et al, 2019). Where examined, the microtubule-containing structures are wider than those lacking microtubules (Önfelt et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…SuHV-1 infected cells formed nanotubes and the presence of intact virions was clearly visible inside nanotubes. The nanotubes formed by SuHV-1 infected cells were remarkably stable compared to most TNTs described (Favoreel et al, 2005;Jansens et al, 2017). The Us3 induced TNTs contained stabilized microtubules and the virus particles were individually transported in membrane-bound vesicles and released along the TNTs and at the contact area between a TNT and adjacent cell.…”
Section: Herpesviridaementioning
confidence: 95%
“…The Us3 induced TNTs contained stabilized microtubules and the virus particles were individually transported in membrane-bound vesicles and released along the TNTs and at the contact area between a TNT and adjacent cell. Contact between Us3-induced TNTs and acceptor cells was very stable and rich for components of adherens junctions such as beta-catenin or E-cadherin at the contact area (Jansens et al, 2017) (Fig. 1).…”
Section: Herpesviridaementioning
confidence: 99%